A QUALITATIVE ASSESSMENT OF THE LABELING INFORMATION OF COLLAGEN-CONTAINING FOOD SUPPLEMENTS - Ile-Jokste, Baiba; Šukele, Renāte (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The use of collagen dietary supplements (CDS) has increased dramatically, creating a large market for these products. With so many options available, it is important for consumers and medical professionals to be well-informed about the composition of these supplements. The aim of this study was to compare the information provided on the labels of CDS with science-based literature. The study conducted an electronic search of randomized, double-blind, control, and pilot studies, which all evaluated the use of oral native or hydrolyzed CDS. All studies were searched in PubMed, and had to be published in English between 2009-2022, August in PubMed. After the initial search, 33 were used for analysis. These studies were then compared to 147 CDS labels registered with the Food Veterinary Service (FVS) in Latvia. The results showed that while studies confirm the benefits of CDS for health, the labels registered in FVS often lack important information about the collagen source, dosage, and duration of use. This results in a significant frequency of errors and potential misuse compared to current scientific knowledge. This makes it challenging for consumers and medical professionals to make informed decisions when purchasing and using collagen supplements.